POLA INTERAKSI GURU DAN SISWA KELAS X SMAN 1 JORONG - Dwi Rahmanto (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2020)
Abstract The Interaction Pattern of Teachers and Students of Class X of SMAN 1 Jorong. This study aims to describe (1) the pattern of intervention, (2) the pattern of adjacent pairs, and (3) the pattern of preference in the interaction discourse of teachers and students of class X at Jorong 1 Public High School during the teaching and learning process. The approach used in this study is a qualitative approach with descriptive methods. Sources of data collected in the form of oral speeches that occur during teaching-learning interactions. Data collection uses documentation techniques. Data analysis techniques use qualitative analysis techniques. From the results of data analysis and research conclusions, the findings are as follows: Interruptive patterns in teacher discourse and class x students at Jorong 1 State Senior High School during the teaching and learning process. The teacher's interruption pattern to students is due to weak student volume and to stop doubts or reinforce the answers to the teacher's questions. The pattern of contiguous pairs occurs normally or naturally according to the stimulus-response process and meets the structure of adjacent pairs which creates habits and regularity. This pattern of well-implemented preferences can be seen from the structure of the preferred action expected to be in the next action and not to be expected to be expected in the next action. Key words: teacher and student interaction, interrupt pattern, contiguous pair pattern, preference pattern … Pola Interaksi Guru dan Siswa Kelas X SMAN 1 Jorong. Penelitian ini bertujuan untuk mendeskripsikan (1), pola interupsi (2),pola pasangan berdekatan, dan (3), pola preferensi dalam wacana interaksi guru dan siswa dalam kelas X di SMA Negeri 1 Jorong pada waktu proses belajar-mengajar. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Sumber data yang dikumpulkan berupa tuturan-tuturan lisan yang terjadi saat interaksi belajar-mengajar. Pengumpulan data menggunakan teknik dokumentasi. Teknik analisis data menggunakan teknik analisis kualitatif. Dari hasil analisis data dan kesimpulan penelitian, diperoleh temuan antara lain sebagai berikut: Pola interupsi dalam wacana guru dan siswa kelas X di SMA Negeri 1 Jorong pada waktu proses belajar-mengajar. Pola interupsi guru kepada siswa dikarenakan volume suara siswa lemah dan untuk menghentikan keraguan atau mempertegas jawaban atas pertanyaan guru. Pola pasangan berdekatan terjadi dengan normal atau alamiah sesuai dengan proses stimulus-respon dan memenuhi struktur pasangan berdekatan yang menimbulkan kebiasaan dan keteraturan.Pola preferensi terlaksana dengan baik ini bisa dilihat dari adanya struktur tindakan yang disukai diharapkan ada pada tindakan berikutnya dan tidak disukai diharapkan tidak ada pada tindakan berikutnya. Kata-kata kunci: interaksi guru dan siswa, pola interupsi, pola pasangan berdekatan, pola preferensi